Natural polyphenols for sustainable active, smart, and intelligent food packaging: a structured narrative review - Dutta, Kunal; Förster, Carola Y.; Orlova, Olga Yu; Dandekar, Thomas; Skorb, Ekaterina V.; Shityakov, Sergey (Frontiers in Food Science and Technology, 2025)
Food packaging offers essential food safety to the consumers. Conventional plastic-based food packaging offers only ordinary physical protection and may sometimes accelerate plastic pollution. Approximately one-third of all packaged foods are known to spoil in the supply chain mainly because of ordinary food packaging. Active, smart, intelligent, and nanocomposite food packaging measures offer many advantages over conventional food packing to retain quality while ensuring extended shelf-life. Natural fruits, vegetables, and tea are abundant source of polyphenols. Notably, recent trends in research demonstrate the utilization of natural polyphenols sourced from food-waste materials for sustainable use in active/smart/intelligent/nanocomposite food packaging. In this narrative review, we explore studies on active, smart, and intelligent food packaging films prepared using natural and food-waste polyphenols. The active packaging films/pads prepared using food-waste polyphenols and fruit polyphenols offer excellent antibacterial, antioxidant, antibrowning, and health-friendly effects. Thus, active, smart, and intelligent packaging materials using natural and food-waste polyphenols help to extend the shelf life of food and ensure minimal wastage of packed food. In addition, some of the active packaging films are edible while some others are biodegradable. In conclusion, the present review is expected to be helpful for promoting more sustainable use of food-waste-polyphenol-based active, smart, and intelligent food packing research.